Eco-Friendly Bioleaching: Innovative Technology for Extracting Critical Raw Materials From WEEE - Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka; Marina Bajić (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
The rapid growth of the quantity of generated electronic waste (e-waste), driven by the increasing demand for electrical and electronic equipment (EEE), has raised urgent concerns regarding its environmental and health impacts. E-waste is the fastest-growing global waste stream, with only a small fraction recycled sustainably. Printed circuit boards (PCBs), a major component of e-waste, contain valuable metals and hazardous substances, complicating recycling efforts. This study explores bioleaching as an environmentally friendly alternative to traditional recycling methods. Bioleaching, utilising microorganisms such as Acidithiobacillus ferrooxidans and A. thiooxidans, which can effectively extracts metals like copper, nickel, and zinc from e-waste, reducing environmental contamination. Our research, conducted under the EIT RawMaterials WEEE-NET9 project, focuses on bioleaching's potential for sustainable recovery of critical raw materials (CRMs) from e-waste. Results demonstrate the effectiveness of bioleaching in metal extraction, supporting the EU's goals of increasing CRM recycling and reducing reliance on primary sources for critical materials, which we have to import into the EU.